A feature space-based business model quality evaluation method - Wang, Zhongjie (Array, 2008)
It is inevitable that there are more or less diversities between business models created by different modelers, thus it is necessary to evaluate and compare them quantitatively to help decision makers discover whose models are pressing much closer to customer requirements. In this paper, a new approach for business model quality evaluation is presented. In order to deal with business models described by varied modeling languages, a unified and extended feature modeling technique is adopted. Quality of a user created model is then measured from two views “completeness” and “soundness” by assessing the distance between the user model and the standard model with the help of feature space as the tools. An example is briefly shown along with each concept and algorithm for illustration. Benefits and deficiencies of our method are briefly concluded for future works